2020
DOI: 10.1016/j.jns.2020.117096
|View full text |Cite
|
Sign up to set email alerts
|

Neurological involvement associated with COVID-19 infection in children

Abstract: We read with great interest the recently published articles regarding neurological involvement associated with COVID-19 infection by Asadi-Pooya et al. and Roman et al. [1,2]. Compared with adult patients, children account for only 1-5% of COVID-19 (SARS-CoV-2) cases, of which more than 80% are asymptomatic or mild cases [3]. SARS-CoV-2 may have neuroinvasive potential because 36% of adult patients are reported to have a variety of neurological manifestations, including headache, dizziness, acute cerebrovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
2
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 14 publications
5
62
2
6
Order By: Relevance
“…The condition was reversible, and the patient achieved full recovery [ 103 ]. Neurological complications of COVID-19 seem to be higher in children with multisystem inflammatory syndrome (MIS-C) [ 104 ]. Reviewing 187 children with MIS-C from six studies showed a high incidence of neurological complications in MIS-C patients with COVID-19.…”
Section: Covid-19 Associated Neurological Symptoms In Pediatricsmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition was reversible, and the patient achieved full recovery [ 103 ]. Neurological complications of COVID-19 seem to be higher in children with multisystem inflammatory syndrome (MIS-C) [ 104 ]. Reviewing 187 children with MIS-C from six studies showed a high incidence of neurological complications in MIS-C patients with COVID-19.…”
Section: Covid-19 Associated Neurological Symptoms In Pediatricsmentioning
confidence: 99%
“…Neurological manifestations included headache, meningism and mental status alteration. Interestingly, most patients achieved full recovery with IV immunoglobulins or steroid treatment [ 104 ]. In another study, Abdel-mannan and colleagues reported four cases of MIS-C with COVID-19 neurological complications.…”
Section: Covid-19 Associated Neurological Symptoms In Pediatricsmentioning
confidence: 99%
“… 7 It was within this subcohort of COVID-19 cases that neurological manifestations of SARS-CoV-2 infection were first identified in children. 8 A review of multiple studies identified an unexpectedly high incidence of neurological symptoms (34%) in children with MIS-C. 9 …”
Section: Introductionmentioning
confidence: 99%
“…And, in the CNS, the recently described Kawasaki disease (KD)-like “multisystem inflammatory syndrome in children” (MIS-C) following SARS-CoV-2 infection appears to be associated with an acute, neuroinflammatory response, which predisposes children to cerebral edema, hemorrhage, stroke, and aseptic meningitis. 10 …”
Section: Introductionmentioning
confidence: 99%